PENERAPAN ASAS ULTIMUM REMEDIUM PADA PELAKU TINDAK PIDANA PELANGGARAN BAKU MUTU LIMBAH (ANALISIS PASAL 100 UU 32 TAHUN 2009) - Reza Meilanda Lesmana (UIN Sunan Gunung Djati Bandung, 2020)
Regarding the crime of violation of waste quality standards stipulated in Law 32 of 2009 article 100 states that in essence every violator of waste quality standards on water quality, emissions, quality of disturbance can be punished, with a maximum imprisonment of three years and a maximum fine of three billion rupiah; Such a crime can only be imposed if the administrative sanctions that have been imposed are not obeyed or the violation is committed more than once. Therefore, from paragraph 2 article 100 is the principle of ultimum remedium in UUPPLH. Ultimum remedium was originally coined by the Dutch Minister of Justice, Mr. Modderman, according to which the principle emphasizes that what can be punished is: (1) violation of the law which is cinditio sine que non, (2) which is punishable is a violation of the law which according to experience cannot be eliminated by other means.